1917 Minn. Laws 839-40 - (:unkn) unknown (My University, 1917)
An Act . . . Making It Unlawful for Any Such Foreign Born Resident to Either Own or Be Possessed of a Shot-gun or Rifle or Other Firearms of Any Make, ch. 500, § 1: Prohibited noncitizens from possessing firearms " of any make. "
Keywords: POSSESSION - DANGEROUS PERSONS